PEMANFAATAN AUGMENTED REALITY UNTUK MENINGKATKAN PEMAHAMAN KONSEP ABSTRAK PADA SISWA SEKOLAH DASAR - Leo Adhar Effendi; Muhammad Ilyas; Arimuliani Ahmad; Suci Ermalisa; Niken Fatricia (JPMUJ, 2026)
The ongoing growth of digital technology has brought meaningful changes to learning practices in primary education, especially in helping students understand science concepts that are abstract in nature. In elementary classrooms, students often struggle to grasp such concepts due to the lack of learning media that are concrete, interactive, and able to support deeper conceptual understanding. This community service program was designed to respond to this challenge by integrating Augmented Reality (AR) as an innovative learning medium in science instruction at SD IT Al Munir Pekanbaru. The activity concentrated on science topics related to living organisms, including land and aquatic organisms, their habitats, and the distinction between beneficial and harmful living things. The primary aim of the program was to improve students’ understanding of abstract science concepts while also fostering higher learning motivation through the use of interactive AR-based media. A descriptive qualitative approach was applied, encompassing stages of preparation, classroom implementation, observation, and evaluation to ensure the activity was carried out in a structured manner. Learning activities utilized the Belajar Makhluk Hidup IPA application, which allows students to interact directly with three-dimensional virtual objects using mobile devices during lessons. Data were gathered through classroom observations, student discussions, and direct feedback, and were supported by relevant literature to strengthen the analysis. The distinctive aspect of this program lies in the real-time use of AR technology that enables students to explore three-dimensional representations of science objects, thereby transforming abstract concepts into more concrete and contextual learning experiences. The findings indicate that students showed higher engagement, enthusiasm, and active participation, as evidenced by their improved ability to explain characteristics, habitats, and classifications of living organisms. Overall, the use of Augmented Reality in science learning proved effective in enhancing students’ motivation and conceptual understanding, while also demonstrating the importance of combining pedagogical planning, effective classroom management, and technological innovation to support sustainable implementation in primary education settings.